HIV and Schistosoma Co-Exposure Leads to Exacerbated Pulmonary Endothelial Remodeling and Dysfunction Associated with Altered Cytokine Landscape - Sandra Medrano-Garcia; Daniel Morales-Cano; Bianca Barreira; Alba Vera-Zambrano; Rahul Kumar; Djuro Kosanovic; Ralph Theo Schermuly; Brian B. Graham; Francisco Perez-Vizcaino; Alistair Mathie; Rajkumar Savai; Soni Pullamseti; et al. (Cells, 2022)
HIV and Schistosoma infections have been individually associated with pulmonary vascular disease. Co-infection with these pathogens is very common in tropical areas, with an estimate of six million people co-infected worldwide. However, the effects of HIV and Schistosoma co-exposure on the pulmonary vasculature and its impact on the development of pulmonary vascular disease are largely unknown. Here, we have approached these questions by using a non-infectious animal model based on lung embolization of Schistosoma mansoni eggs in HIV-1 transgenic (HIV) mice. Schistosome-exposed HIV mice but not wild-type (Wt) counterparts showed augmented pulmonary arterial pressure associated with markedly suppressed endothelial-dependent vasodilation, increased endothelial remodeling and vessel obliterations, formation of plexiform-like lesions and a higher degree of perivascular fibrosis. In contrast, medial wall muscularization was similarly increased in both types of mice. Moreover, HIV mice displayed an impaired immune response to parasite eggs in the lung, as suggested by decreased pulmonary leukocyte infiltration, small-sized granulomas, and augmented residual egg burden. Notably, vascular changes in co-exposed mice were associated with increased expression of proinflammatory and profibrotic cytokines, including IFN-γ and IL-17A in CD4+ and γδ T cells and IL-13 in myeloid cells. Collectively, our study shows for the first time that combined pulmonary persistence of HIV proteins and Schistosoma eggs, as it may occur in co-infected people, alters the cytokine landscape and targets the vascular endothelium for aggravated pulmonary vascular pathology. Furthermore, it provides an experimental model for the understanding of pulmonary vascular disease associated with HIV and Schistosoma co-morbidity.